Selected Aspects of Internationalization in the Liberec Region and the Free State of Saxony - Potužáková, Zuzana; Demel, Jaroslav (Journal of Reviews on Global Economics, 2023)
Internationalization is a widely discussed topic analysed from various points of view. In our paper, we have decided to measure this trend in two border regions in former Eastern Germany and in Czechia, namely in Saxony and the Liberec region in the time period 2013-2020. Both areas belonged to the Eastern bloc before 1990. Saxony experienced a rapid reunification process within the early 1990s and Czechia a transformation process competed in 2004 by the EU accession. In our paper, we have decided to test three hypotheses. First, we tested if Saxony is more internationalized in terms of human resources (1) and secondly with regard to export output (2). Then, we conducted the same tests on the Liberec region. Our assumption was that, due to the rapid reunification and favourable geographic proximity of lucrative Western markets, the position of Saxony would be more advanced. Finally, we tested the hypothesis (3) that the rising number of foreign workers contribute to the rising export volumes. We correlated the indicators of employed foreigners and exports per head in both regions from 2013 to 2020.